2012
DOI: 10.4161/derm.20965
|View full text |Cite
|
Sign up to set email alerts
|

Role of solar UVB irradiance and smoking in cancer as inferred from cancer incidence rates by occupation in Nordic countries

Abstract: A large body of evidence indicates that solar ultraviolet-B (UVB) irradiance and vitamin D reduce the risk of incidence and death for many types of cancer. However, most of that evidence comes from midlatitude regions, where solar UVB doses are generally high in summer. Data on cancer standardized incidence ratios (SIRs) by sex and 54 occupation categories based on 1.4 million male and 1.36 million female cancer cases for 1961–2005 in the five Nordic countries provide the basis for an ecological study of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 50 publications
2
52
0
1
Order By: Relevance
“…The prevalence of vitamin D deficiency was highest in managers, professionals, and related workers compared with skilled agricultural, forestry, and fishery workers. These results are consistent with previous studies in Korea [3,28] and other countries [29][30][31]. This result may be because subjects who are classified as managers, professionals, and related workers are usually indoors and do not receive adequate sunlight exposure.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of vitamin D deficiency was highest in managers, professionals, and related workers compared with skilled agricultural, forestry, and fishery workers. These results are consistent with previous studies in Korea [3,28] and other countries [29][30][31]. This result may be because subjects who are classified as managers, professionals, and related workers are usually indoors and do not receive adequate sunlight exposure.…”
Section: Discussionsupporting
confidence: 83%
“…Patterns of morbidity and mortality from cancer is different for each gender and age, as well as ethnicity, first of all determined by the physiological characteristics of the organism and then exposure to modifiable risk factors (Jemal et al, 2011;Shin et al, 2012;Jung et al, 2012). The incidence of cancer of the larynx also has statistical differences according to age and sex (Wunsch, 2004;de Souza et al, 2011), geographical features of the place of residence (Dykhno et al, 2002;Saurina et al, 2010), social class and the living standards of the studied group of population (Vassileiou et al, 2012) and a number of other external factors (Wong et al, 1993;Grant, 2012;Romanowicz-Makowska et al, 2012). In Kazakhstan, it has already been shown that there is geographical variation in incidences of breast (Bilyalova et al, 2012), esophageal (Igissinov S et al, 2012;2013), and cervical cancer , with changes over time (Igissinov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cancer of the larynx also has statistical differences according to age and sex (Wunsch, 2004;de Souza et al, 2011), geographical features of the place of residence (Dykhno et al, 2002;Saurina et al, 2010), social class and the living standards of the studied group of population (Vassileiou et al, 2012) and a number of other external factors (Wong et al, 1993;Grant, 2012;Romanowicz-Makowska et al, 2012). In Kazakhstan, it has already been shown that there is geographical variation in incidences of breast (Bilyalova et al, 2012), esophageal (Igissinov S et al, 2012;2013), and cervical cancer , with changes dover time (Igissinov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%